2016
DOI: 10.1063/1.4958951
|View full text |Cite
|
Sign up to set email alerts
|

Full-dimensional quantum dynamics of CO in collision with H2

Abstract: We report the first full-dimensional potential energy surface (PES) and quantum mechanical close-coupling calculations for scattering of SiO due to H 2. The full-dimensional interaction potential surface was computed using the explicitly correlated coupled-cluster (CCSD(T)-F12b) method and fitted using an invariant polynomial approach. Pure rotational quenching cross sections from initial states v 1 = 0, j 1 =1-5 of SiO in collision with H 2 are calculated for collision energies between 1.0 and 5000 cm −1. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 66 publications
(88 reference statements)
0
46
0
Order By: Relevance
“…19,20 We found this to be impossible for two reasons. The first problem is with the long-range behavior of that potential, which fails to decay to zero at long range if the intramolecular distances r and s differ from their equilibrium values.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 We found this to be impossible for two reasons. The first problem is with the long-range behavior of that potential, which fails to decay to zero at long range if the intramolecular distances r and s differ from their equilibrium values.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 PES using the (original) intermonomer potential subroutine from the Supporting Information of Ref. 20 and adding to it the same intramonomer potentials as used in U tot,15 .…”
Section: H2–co Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…The relaxation pathway was found to be mostly dominated by ∆ j = −1 transitions, for temperatures in the 1-1000 K range. In a more recent work, Yang et al 168,169 reported the first full-dimensional computation of rovibrational transitions in CO by H 2 at temperatures ranging from 1-100 K. Complex scattering lengths for collisions of linear and non-linear polyatomic molecules, CO 2 , H 2 O and NH 3 , with He have recently been reported by Yang and co-workers. 170 The ratio of the imaginary to real components of the scattering length, β/α, was found to generally increase with decreasing rotational constant.…”
Section: B Quasiresonant Rotational and Vibrational Transfer In Molementioning
confidence: 96%
“…and compared against 6D-CC results obtained perviously 15 . Figure 2 shows elastic and rotationally inelastic cross sections for the (1, 1, 0, 0) initial state.…”
Section: Previous Workmentioning
confidence: 99%